Peran Anggota Keluarga Berketahanan Dalam Perspektif Quran - Muhammad Ridho Hisyam; Suyanto Suyanto; Muhammad Sadzili; Zainul Arifin; Ahmad Syafi'i Rahman (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2019)
This study aims to identify the verses of the Quran relating to family resilience. The focus is on the ideal role of each family member; father, mother and child; in strengthening resilience in their environment. From there it can be seen that each one needs seriousness in behaving, acting and communicating with each other for the sake of the continuity of family life can be maintained, if we need to ask for help from other parties. For this reason, it is recommended that family security legislation, especially in Indonesia, be carried out immediately in addition to the activeness of Islamic religious leaders participating directly in the success of its implementation by spreading it as part of the nation's resilience